Texts and Contexts Reflections in Pacific Islands Historiography - Ballard, Chris; Brady, Ivan; Campbell, I. C.; Douglas, Bronwen; Goldsmith, Michael; Hanlon, David; Howe, K. R.; Lal, Brij V.; Lal, Brij V.; Laracy, Hugh; Lindstrom, Lamont; Munro, Doug; et al. (University of Hawaii Press, 2005)
Texts and Contexts is concerned with the development of Pacific Islands history as a specialization in its own right. Specifically, this volume examines the foundational texts that pioneered and consolidated the new subdiscipline and served as the building blocks and stepping stone for further developments in the field. Thirty-five texts, all of which represent defining points in the development of Pacific Islands historiography, are examined. Much more than retrospective appraisals of the foundational texts, the individual chapters consider a text or complimentary texts within the context of the time of writing and gauge what ongoing influence they exerted. In some cases they suggest how a particular text has been superseded by subsequent work that breaks new conceptual ground in the ongoing process of revisionism. Contributors: Chris Ballard on Gavin Souter; Ivan Brady on Greg Dening; I. C. Campbell on Norma McArthur; Bronwen Douglas and Doug Munro on H. E. Maude and Dorothy Shineberg; Michael Goldsmith on Marshall Sahlins; David Hanlon on Francis X. Hezel; K. R. Howe on Andrew Sharp and David Lewis; Brij V.Lal on K. L. Gillion and Peter Corris; Hugh Laracy on Niel Gunson and Ta'unga; Lamont Lindstrom on Peter Worsley and Peter Lawrence; Doug Munro on Douglas L. Oliver, R. P. Gilson, J. W. Davidson, and K. R. Howe; Vincent O'Malley on Keith Sinclair and Alan Ward; Jon Osorio on Ralph Kuykendall and Gavan Daws; Tom Ryan on Bernard Smith; Jane Samson on W. P. Morrell and Deryck Scarr; Francis West on Francis West and Gavan Daws; Glyndwr Williams on O. H. K. Spate